2003
DOI: 10.1097/01.lab.0000092229.93203.57
|View full text |Cite
|
Sign up to set email alerts
|

A Crucial Role of Hepatocyte Nuclear Factor-4 Expression in the Differentiation of Human Ductular Hepatocytes

Abstract: SUMMARY: Ductular structures are suggested to be bipotential progenitor cells that may differentiate into hepatocytes or biliary epithelial cells (BEC). To better understand the differentiation process, we studied the expression of hepatocyte nuclear factor (HNF) in ductular structures. Matured hepatocytes in normal liver expressed HNF-1, HNF-4␣, HNF-3␤, and C/EBP␣ in the nucleus. Normal BEC expressed HNF-1 but did not express HNF-4␣, suggesting an important role of HNF-4␣ in maintaining the phenotype of matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…In addition to its nuclear localization in hepatocytes, HNF4α was highly expressed in the cytoplasmic compartment in DR and fibrotic areas (white arrow). Prior studies showed cytoplasmic expression of HNF4α messenger RNA in ductular hepatocytes in massive necrosis areas . The subcellular localization of HNF4α could be associated with its phosphorylation status .…”
Section: Resultsmentioning
confidence: 95%
“…In addition to its nuclear localization in hepatocytes, HNF4α was highly expressed in the cytoplasmic compartment in DR and fibrotic areas (white arrow). Prior studies showed cytoplasmic expression of HNF4α messenger RNA in ductular hepatocytes in massive necrosis areas . The subcellular localization of HNF4α could be associated with its phosphorylation status .…”
Section: Resultsmentioning
confidence: 95%
“…An extensive ductular reaction occurs after massive (or submassive) hepatic necrosis in humans 47–53. In this type of injury, ductular proliferation involves mature cholangiocytes and ductular hepatocytes.…”
Section: Oval Cell Differentiation In Massive Hepatic Necrosis In Humansmentioning
confidence: 99%
“…It has been reported that the HNF6 and HNF1β are important in biliary development, 15 while HNF1α and HNF4α are important in hepatocyte specification. 16,17 We assessed biliary and hepatic marker expression by quantitative PCR. We observed significant upregulation in HNF6 expression on PU134 and laminin (both 1.6-fold induction, p <0.001), and in HNF1β expression (1.4-fold, p <0.001; and 1.6-fold, p <0.05, respectively) when compared to the plastic controls (Fig.…”
Section: Resultsmentioning
confidence: 99%